Impact of patients' perception of COPD and treatment on adherence and health-related quality of life in real-world: Study in 53 community pharmacies. (January 2021) - López-Pintor, E.; Grau, J.; González, I.; Bernal-Soriano, MC; Quesada, J.A.; Lumbreras, B.
Abstract: Background: Patient adherence to treatment in chronic obstructive pulmonary disease (COPD) is essential to optimize disease management. We aimed to assess the impact of patients' perception of their treatment and disease on adherence and Health-Related Quality of Life (HRQL) in patients attending a community pharmacy, where usually subjects have a better condition than those in clinical settings. Methods: We performed a cross-sectional study of 318 patients with COPD in treatment with inhalers in the last 3 months from 53 community pharmacies. We assessed HRQL with St George's Respiratory Questionnaire (SGRQ). Persistence was assessed from the three previous refills and adherence through the Test of Adherence to Inhalers test. Results: Persistence was achieved by 78.6% of the patients and 58.5% had good adherence. Patients having a multidose DPI and those with MDI showed a 2.8-fold and 4.1-fold increased association, respectively, with intermediate/poor adherence in comparison with those having a single dose DPI. Those patients who did not have knowledge about COPD (aOR 2.106, p = 0.006) and those who thought that the inhaler effectiveness was fair/poor (aOR 2.361, p = 0.006) were more likely to have intermediate/poor adherence. Overall SGRQ score was significantly worse in patients with intermediate/poor adherence (p = 0.036) and in those who thought the inhaler's effectiveness was fair/poor (p < 0.001). Conclusions: The type of inhaler and patients' knowledge and perceptions of their disease and treatment were associated with good adherence and higher HRQL. Clinicians should promote shared-decision making in the choice of inhaler depending on patients' individual abilities and beliefs. Highlights: Patients in real world show a high rate of persistence and low rate of adherence. Patients with critical errors in the management of the inhaler show worse perception of its effectiveness. Patient's perception of inhaler effectiveness was associated with adherence and HRQL. Smoking habit, type of inhaler and patients' knowledge on COPD were associated with adherence. Adherence was associated with higher levels of HRQL.